2014
DOI: 10.1007/s00408-014-9661-y
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Intervention Within the Framework of a Lung Cancer Screening Program: Preliminary Results and Clinical Perspectives from the “Cosmos-II” Trial

Abstract: Data coming from the literature investigating the effectiveness and interaction between smoking cessation (SC) and lung cancer screening (LCScr) are still sparse and inconsistent. Herein, we report the preliminary results from the ongoing lung cancer screening trial ("Cosmos-II") focusing our analysis on the inter-relationship between the SC program and the LCScr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
1
16
0
1
Order By: Relevance
“…However, there is some evidence that a positive screening test result increases the smoking cessation rate 11. Our own data from the Cosmos-II trial (CT lung cancer screening in Italian population) support this 9. Similar to UKLS, we found that ‘high-risk’ subjects, according to a personalised risk model, requiring an additional CT scan were more likely to quit smoking compared with ‘low-risk’ subjects.…”
supporting
confidence: 71%
“…However, there is some evidence that a positive screening test result increases the smoking cessation rate 11. Our own data from the Cosmos-II trial (CT lung cancer screening in Italian population) support this 9. Similar to UKLS, we found that ‘high-risk’ subjects, according to a personalised risk model, requiring an additional CT scan were more likely to quit smoking compared with ‘low-risk’ subjects.…”
supporting
confidence: 71%
“…More studies on both the positive and negative aspects are required to enrich the conclusion and make further efforts to reduce morbidity and mortality from lung cancer. 26,IC 95%=0,78,P=0,193). Anualmente, o rastreamento de LDCT foi sensível em encontrar mais cânceres de pulmão.…”
Section: Resultsunclassified
“…68 Plasma samples that were prospectively collected during the COSMOS II screening trial have been profiled to set up and validate the clinical utility of the microRNAsignature based miR-Test. 69 The DECAMP-1 and DECAMP-2 prospective observational trials (NCT01785342 and NCT02504697) have been designed to examine a variety of existing biomarkers for lung cancer diagnosis as well as new biomarkers discovered specifically in this clinical setting. DECAMP-1 seeks to improve follow-up of patients with IPNs by determining whether analyzed biomarkers are able to distinguish incidentally detected malignant from benign pulmonary nodules in high-risk smokers, whereas DECAMP-2 will test biomarkers of risk in screened asymptomatic high-risk individuals.…”
Section: Current Trials In Which Biomarkers Are Considered or Includedmentioning
confidence: 99%